Responses of photosynthetic characteristics and enzyme activity of nitrogen metabolism to low nitrogen in maize with different nitrogen tolerance - Ji, Pengtao; Cui, Yongwei; Li, Xiangling; Xiao, Kai; Tao, Peijun; Zhang, Yuechen (International Journal of Agricultural and Biological Engineering, 2020)
Understanding the physiological processes associated with leaf photosynthetic characteristics and nitrogen (N) assimilation during grain-filling stage are helpful for enhancing nitrogen utilization efficiency (NUtE) of maize. In this study, the leaf photosynthetic and N assimilation parameters in maize, including Zhengdan 958 (ZD958), a low-N tolerance cultivar and Huanong 138 (HN138), a low-N sensitive cultivar under different N rates were examined. Results showed that ZD958 displayed significant increases on grain yield and NUtE than that in HN138. Analyses on the leaf photosynthetic and N assimilation-associated processes indicated that ZD958 had higher leaf N remobilization (Rem N), net photosynthetic rate (Pn) and photosynthetic N use efficiency (PNUE) with respect to those of HN138 during grain-filling stage. In addition, ZD958 was also shown to be higher activities of leaf nitrate reductase (NR), glutamine synthetase (GS), nitrate reductase (GDH) and glutamine synthetase (GAGOT) than those of HN138. The leaf PNUE was significantly positively correlated with NR, GS, GDH, GOGAT suggesting that leaf PNUE and NR, GS, GDH, GOGAT jointly determined the N remobilization efficiency and the leaf N remobilization during post-silking. These results suggested that ZD958 possessed improved PNUE, NR and GS activities in leaves during grain-filling stage that contributes improve grain weights and yield formation capacities upon under low-N conditions. Keywords: low-N, photosynthesis, nitrogen assimilation, nitrogen utilization efficiency, maize DOI: 10.25165/j.ijabe.20201306.5891 Citation: Ji P T, Cui Y W, Li X L, Xiao K, Tao P J, Zhang Y C. Responses of photosynthetic characteristics and enzyme activity of nitrogen metabolism to low nitrogen in maize with different nitrogen tolerance. Int J Agric & Biol Eng, 2020; 13(6): 133–143.